The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/hex.12910
|View full text |Cite
|
Sign up to set email alerts
|

Women’s health literacy and the complex decision‐making process to use complementary medicine products in pregnancy and lactation

Abstract: BackgroundLittle is known about women's decision‐making processes regarding using complementary medicine products (CMPs) during pregnancy or lactation.ObjectivesTo explore the decision‐making processes of women choosing to use CMPs in pregnancy and lactation; and to investigate how women's health literacy influences their decisions.Design, setting and participantsIn‐depth interviews and focus group discussions were held with twenty‐five pregnant and/or breastfeeding women. Data were analysed using thematic ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 70 publications
1
24
0
Order By: Relevance
“…38 For instance, adequate health literacy supports pregnant women in deciding to use complementary medicine products. 39 Studies on health literacy in pregnant women are scarce and if they exist, they do not evaluate the change of health literacy as a result of an intervention. 17 To our knowledge, this is the first study assessing the impact of an intervention that aims at improving health literacy in pregnant women and the influence of health literacy on various outcomes during pregnancy, such as GWG, lifestyle and health service use.…”
Section: Discussionmentioning
confidence: 99%
“…38 For instance, adequate health literacy supports pregnant women in deciding to use complementary medicine products. 39 Studies on health literacy in pregnant women are scarce and if they exist, they do not evaluate the change of health literacy as a result of an intervention. 17 To our knowledge, this is the first study assessing the impact of an intervention that aims at improving health literacy in pregnant women and the influence of health literacy on various outcomes during pregnancy, such as GWG, lifestyle and health service use.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the studies excluded from the review presented cross-sectional estimates of micronutrient supplement use in which iron and/or folic acid supplementation were frequently not disaggregated from other supplements 15–27 or complementary and complementary medicine products, which include herbal medicines, topical herbal preparations, vitamin and mineral supplements, and prebiotic and probiotic supplements. 28 29 Several studies considered in full-text review showed evidence of factors influencing the use of prenatal supplements and complementary medical products. However, they did not provide any information on self-management; nor did they report how the use of supplements or outcomes from supplement use differed between self-management and health worker-initiated provision.…”
Section: Discussionmentioning
confidence: 99%
“…First, in many studies, the data clustered micronutrient supplements including iron and/or folic acid supplementation within a broader category of complementary and complementary medicine products, obfuscating the interpretation of study findings. Studies have examined the motivation and use of complementary medical products around the time of pregnancy, 28 29 but the motivations and usage patterns of specific products within the umbrella of complementary medical products likely differs by product. For example, while there is global normative guidance for both use of ginger and chamomile tea for relief of nausea during early pregnancy and IFA during pregnancy and postnatal, 3 the reasons and likelihood of self-management for the use of herbal teas in pregnancy and the self-management of iron and/or folic acid supplements will be vastly different regarding the quality and type of evidence available.…”
Section: Discussionmentioning
confidence: 99%
“…However, older people have been reported to use CM covertly (Rayner & Bauer, 2016) and are prone to polypharmacy (Mohamed et al, 2020), placing them at an increased risk for an adverse drug event and mortality. Reasons for CM use vary, with research showing that when conventional therapies are limited, or there is an unwillingness to use them, CM uptake may increase (Barnes et al, 2019; Jones et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…At present, there is no cure or prevention for dementia, with pharmaceutical treatments only able to alleviate early symptoms, without slowing its degenerative course. This lack of effective conventional therapies for dementia is likely to result in increased CM use (Barnes et al, 2019; Jones et al, 2019).…”
Section: Introductionmentioning
confidence: 99%